Hemangiomatous ameloblastoma: report of a case - A. O. Adisa; A. O. Lawal; A. A. Olusanya; J. T. Arotiba (Nigerian Dental Journal)
Hemangiomatous ameloblastoma is a rare variant of ameloblastoma with only a few cases reported in the English literature. This is a report of a 42 year old man with a recurrent mandibular neoplasm who had r epeated surgical interventions. Clinical and radiographic examinations were not significantly different from other regular variants of ameloblastoma. Microscopic examination however revealed islands of cuboidal and columnar cells arranged in a pallisaded pattern with a central area of squamous metaplasia and stellate reticulum-like cells. There were multiple vascular channels containing red blood cells within the stellate reticulum-like areas. Surgical resection of the mandibular mass was done with immediate reconstruction. It may be concluded that repeated surgical interventions may be a possible etiology for the development of hemangiomatous ameleblastoma.